Antibacterial repairing device and preparation method thereof
By using a hydrogel layer loaded with nano zinc oxide and a puffed polytetrafluoroethylene film layer in the anti-adhesion repair material, combined with a polymer mesh layer, the problem of existing repair materials being easily caused by infection in the abdominal cavity is solved, and the problem of existing repair materials being easily caused by infection is achieved. Long-term anti-adhesion and effective antibacterial effects.
Patent Information
- Application Number
- CN202411654732.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-19
AI Technical Summary
Existing anti-adhesion repair materials are prone to infection in the abdominal cavity and have insufficient antibacterial properties, which limits their clinical application.
An antibacterial repair device consisting of a first hydrogel layer, a puffed polytetrafluoroethylene film layer, a second hydrogel layer and a polymer mesh sheet layer are used, and all hydrogel layers are loaded with nano zinc oxide and pass through vacuum. Soaking and freeze-drying techniques improve antibacterial effects.
It achieves long-term anti-adhesion effect, effectively prevents infection, has excellent aging resistance and chemical stability, and significantly improves the antibacterial performance of the repair device.
Smart Images

Figure CN119455130A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials, and in particular relates to an antibacterial repair device and a preparation method thereof. Background Art
[0002] The development of modern laparoscopic surgery has promoted the innovation of repair materials. Polypropylene (PP) has become the most widely used repair material due to its significant stimulation of fibrous tissue proliferation, high tensile strength, economical and good anti-infection properties. However, PP is prone to adhesion when in contact with abdominal viscera, which has prompted the development of a variety of anti-adhesion products.
[0003] A common non-absorbable repair device is the combination of PP and expanded polytetrafluoroethylene (ePTFE), in which the microporous structure of ePTFE faces the internal organs, while the macroporous PP mesh faces the abdominal wall. The stable physical and chemical properties of ePTFE and the porous structure composed of fine fibers are conducive to cell growth and tissue regeneration. At the same time, its soft material and low surface energy (due to its -CF2- structural unit) reduce the adhesion of proteins and cells, thereby reducing the inflammatory response. However, the microporous structure of ePTFE prevents the entry of macrophages, resulting in its weak anti-infection ability. Once an infection occurs, a secondary surgery may be required to remove it, which limits its clinical application.
[0004] In addition, methods of adding absorbable biomaterials to the surface of PP by weaving or chemical bonding have also been explored to form a protective layer to reduce the contact between the internal organs and the repair device until the repair device is covered by tissue. Nevertheless, studies have shown that these absorbable materials cannot completely prevent adhesion, and their adhesion rate is even higher than that of ePTFE.
[0005] Recent studies have pointed out that the new biomaterial polyvinylidene fluoride (PVDF), as an inert, highly crystalline fluorinated polymer, exhibits excellent mechanical, heat resistance, radiation resistance, aging resistance and chemical stability. PVDF patches have less shrinkage, better operability and friction, and low adhesion to surrounding tissues. They can be directly used in the abdominal cavity, thereby improving postoperative comfort and reducing surgical pain. They are an ideal substitute for PP, but their antibacterial properties still need to be improved. Summary of the invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide an antibacterial repair device and a preparation method thereof which can achieve long-term anti-adhesion effect, effectively prevent infection, and have excellent aging resistance and chemical stability.
[0007] The invention provides an antibacterial repair device, comprising a first hydrogel layer, an expanded polytetrafluoroethylene film layer, a second hydrogel layer and a polymer mesh layer which are arranged in sequence; the first hydrogel layer, the expanded polytetrafluoroethylene film layer and the second hydrogel layer are all loaded with nano zinc oxide.
[0008] Preferably, the thickness of the expanded polytetrafluoroethylene film layer is 0.8-2 mm; and the pore size of the expanded polytetrafluoroethylene film layer is not greater than 5 μm.
[0009] Preferably, the edge of the polymer mesh layer is covered with a third hydrogel layer; the third hydrogel layer is loaded with nano zinc oxide.
[0010] Preferably, the first hydrogel layer, the second hydrogel layer and the third hydrogel layer are double-crosslinked alginate-polyvinyl alcohol hydrogels loaded with nano zinc oxide;
[0011] The polymer mesh layer is selected from a polyvinylidene fluoride mesh layer or a polypropylene mesh layer.
[0012] Preferably, the thickness of the first hydrogel layer and the second hydrogel layer are independently 0.6 to 1 mm.
[0013] The present invention also provides a method for preparing an antibacterial repair device, comprising the following steps:
[0014] S1) soaking the expanded polytetrafluoroethylene film in a nano zinc oxide solution under vacuum conditions, and drying the solution to obtain an expanded polytetrafluoroethylene film layer;
[0015] S2) covering the two surfaces of the expanded polytetrafluoroethylene film layer with a hydrogel solution containing nano zinc oxide, and after freeze-drying and thawing, obtaining an expanded polytetrafluoroethylene film layer composited with the first hydrogel layer and the second hydrogel layer;
[0016] S3) Suturing the polymer mesh to the surface of the second hydrogel layer in the expanded polytetrafluoroethylene film layer that composites the first hydrogel layer and the second hydrogel layer to obtain an antibacterial repair device.
[0017] Preferably, after the polymer mesh is sutured in step S3), the edge of the polymer mesh is covered with a hydrogel solution containing nano zinc oxide, and after freeze-drying and thawing, an antibacterial repair device is obtained.
[0018] Preferably, in step S3), after freeze-drying and thawing, the product is immersed in a calcium ion solution and dried to obtain an antibacterial repair device.
[0019] Preferably, the concentration of the nano zinc oxide solution is 1 to 3 g / L;
[0020] The pore size of the expanded polytetrafluoroethylene membrane is not greater than 5 μm; the thickness of the expanded polytetrafluoroethylene membrane is 0.8 to 2 mm;
[0021] The hydrogel solution containing nano zinc oxide is obtained by mixing a polyvinyl alcohol solution containing nano zinc oxide with an alginate solution;
[0022] The mass concentration of polyvinyl alcohol in the polyvinyl alcohol solution containing nano zinc oxide is 8% to 12%; the concentration of nano zinc oxide in the polyvinyl alcohol solution containing nano zinc oxide is 1 to 3 g / L; the mass concentration of alginate in the alginate solution is 1% to 3%;
[0023] The mass ratio of the polyvinyl alcohol solution containing nano zinc oxide to the alginate solution is (7-9): (3-1).
[0024] Preferably, the immersion in step S1) is carried out under a negative pressure environment of 0.06 to 0.1 MPa; the immersion time is 10 to 30 minutes;
[0025] The freeze drying temperature in step S2) is -10°C to -30°C; the freeze drying time is 4 to 8 hours; and the thawing process is carried out at room temperature;
[0026] The freeze drying and thawing steps are repeated after the thawing process in step S2); the freeze drying and thawing processes are repeated 1 to 3 times.
[0027] The present invention provides an antibacterial repair device, comprising a first hydrogel layer, an expanded polytetrafluoroethylene film layer, a second hydrogel layer and a polymer mesh layer arranged in sequence; the first hydrogel layer, the expanded polytetrafluoroethylene film layer and the second hydrogel layer are all loaded with nano zinc oxide. Compared with the prior art, the antibacterial repair device provided by the present invention comprises a hydrogel layer with good biocompatibility, and contains zinc oxide, which can not only be stable for a long time, but also can achieve sustained release, thereby providing a long-term and effective antibacterial effect.
[0028] Furthermore, the edge of the polymer mesh layer is covered with an antibacterial hydrogel, which not only enhances the antibacterial effect but also significantly reduces the inflammatory response around the mesh tissue.
[0029] Furthermore, the present invention uses polyvinylidene fluoride material as the mesh layer, which has obvious advantages in durability and stability and is an ideal material for the repair device.
[0030] The present invention also provides a method for preparing an antibacterial repair device, comprising the following steps: S1) soaking an expanded polytetrafluoroethylene membrane in a nano zinc oxide solution under vacuum conditions, drying, and obtaining an expanded polytetrafluoroethylene membrane layer; S2) covering the two surfaces of the expanded polytetrafluoroethylene membrane layer with a hydrogel solution containing nano zinc oxide, and obtaining an expanded polytetrafluoroethylene membrane layer composited with a first hydrogel layer and a second hydrogel layer after freeze drying and thawing; S3) suturing a polymer mesh to the surface of the second hydrogel layer in the expanded polytetrafluoroethylene membrane layer composited with the first hydrogel layer and the second hydrogel layer, and obtaining an antibacterial repair device. Compared with the prior art, the present invention effectively removes the air in the micropores of the expanded polytetrafluoroethylene membrane through vacuum exhaust technology, avoids the obstruction of the air in the micropores to the adhesion of zinc oxide, and thus improves the antibacterial effect, so that even if pathogens penetrate the antibacterial hydrogel and enter the micropores in the membrane, they can be effectively inhibited to prevent infection. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A schematic diagram of the structure of the antibacterial repair device provided by the present invention;
[0032] Figure 2 A top view of the antibacterial repair device provided by the present invention;
[0033] Figure 3 This is a graph showing the zinc oxide release curve of the ePTFE membrane A loaded with zinc oxide particles prepared in Example 1 of the present invention;
[0034] Figure 4 This is a graph showing the zinc oxide release curve of the gel prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0036] The invention provides an antibacterial repair device, comprising a first hydrogel layer, an expanded polytetrafluoroethylene film layer, a second hydrogel layer and a polymer mesh layer which are arranged in sequence; the first hydrogel layer, the expanded polytetrafluoroethylene film layer and the second hydrogel layer are all loaded with nano zinc oxide.
[0037] The antibacterial repair device provided by the present invention comprises a hydrogel layer having good biocompatibility and contains zinc oxide, which is not only stable for a long time but also can achieve sustained release, thereby providing a long-term and effective antibacterial effect.
[0038] See also Figure 1 and Figure 2 ; Figure 1 A schematic diagram of the structure of the antibacterial repair device provided by the present invention; Figure 2 This is a top view of the antibacterial repair device provided by the present invention.
[0039] The antibacterial repair device provided by the present invention comprises an expanded polytetrafluoroethylene film layer; the thickness of the expanded polytetrafluoroethylene film layer is preferably 0.8-2 mm, more preferably 0.8-1.5 mm, and even more preferably 1 mm; the pore size of the expanded polytetrafluoroethylene film layer is preferably not greater than 5 μm.
[0040] The upper and lower surfaces of the expanded polytetrafluoroethylene film layer are respectively provided with a first hydrogel layer and a second hydrogel layer; the first hydrogel layer and the second hydrogel layer are both loaded with nano zinc oxide; specifically, the first hydrogel layer and the second hydrogel layer are double cross-linked alginate-polyvinyl alcohol hydrogels loaded with nano zinc oxide; further specifically, the first hydrogel layer and the second hydrogel layer are double cross-linked sodium alginate-polyvinyl alcohol (PVA) hydrogels loaded with nano zinc oxide; the present invention does not control the thickness of the first hydrogel layer and the second hydrogel layer, and it is recommended that the thickness of the first hydrogel layer and the second hydrogel layer is independently 0.6 to 1 mm. The present invention loads nano zinc oxide through a double cross-linked network constructed by PVA and alginate, so that zinc oxide can be stably combined in the hydrogel for a long time and achieve sustained release, thereby providing a long-term and effective antibacterial effect.
[0041] A polymer mesh layer is arranged on the surface of the second hydrogel layer away from the expanded polytetrafluoroethylene film layer; the polymer mesh layer is preferably arranged on the surface of the second hydrogel layer away from the expanded polytetrafluoroethylene film layer by suturing; the suturing preferably uses polytetrafluoroethylene (PTFE) sutures; the polymer mesh layer is preferably a polymer warp knitted mesh layer; the thickness of the polymer mesh layer is preferably 0.4 to 0.8 mm, more preferably 0.4 to 0.6 mm, most preferably 0.5 mm; the pore size of the polymer mesh layer is preferably 0.1 to 2 mm , more preferably 0.5-2mm, and even more preferably 1-2mm; the polymer mesh layer is preferably a polyvinylidene fluoride (PVDF) mesh layer or a polypropylene (PP) mesh layer; compared with PP, PVDF exhibits better hydrolysis resistance and degradation resistance after 6 months of implantation in animals, and no cracks appear on its surface, while cracks appear on PP, which shows that PVDF has obvious advantages in durability and stability and is an ideal repair device material. Therefore, the present invention preferably uses a polyvinylidene fluoride (PVDF) mesh layer as the polymer mesh layer.
[0042] According to the present invention, further, the edge of the polymer mesh layer is covered with a third hydrogel layer; the third hydrogel layer is loaded with nano zinc oxide; the third hydrogel layer is a double cross-linked alginate-polyvinyl alcohol hydrogel loaded with nano zinc oxide; more specifically, the third hydrogel layer is a double cross-linked sodium alginate-polyvinyl alcohol hydrogel loaded with nano zinc oxide; the present invention does not have any special control on the thickness of the third hydrogel layer, and it only needs to completely cover the edge of the polymer mesh layer. The edge of the polymer mesh layer is covered with a hydrogel with antibacterial properties, which not only enhances the antibacterial effect, but also significantly reduces the inflammatory response around the mesh tissue.
[0043] The present invention also provides a method for preparing the above-mentioned antibacterial repair device, comprising the following steps: S1) soaking an expanded polytetrafluoroethylene film in a nano zinc oxide solution under vacuum conditions, and drying to obtain an expanded polytetrafluoroethylene film layer; S2) covering the two surfaces of the expanded polytetrafluoroethylene film layer with a hydrogel solution containing nano zinc oxide, and after freeze-drying and thawing treatment, obtaining an expanded polytetrafluoroethylene film layer composited with a first hydrogel layer and a second hydrogel layer; S3) suturing a polymer mesh to the surface of the second hydrogel layer in the expanded polytetrafluoroethylene film layer composited with the first hydrogel layer and the second hydrogel layer to obtain an antibacterial repair device.
[0044] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.
[0045] Under vacuum conditions, an expanded polytetrafluoroethylene membrane is immersed in a nano zinc oxide solution and dried to obtain an expanded polytetrafluoroethylene membrane layer; the thickness of the expanded polytetrafluoroethylene membrane is preferably 0.8-2 mm, more preferably 0.8-1.5 mm, and more preferably 1 mm; the pore size of the expanded polytetrafluoroethylene membrane is preferably not greater than 5 μm; the concentration of the nano zinc oxide solution is preferably 1-3 g / L, more preferably 1-2 g / L; specifically, the nano zinc oxide solution is prepared according to the following steps: mixing nano zinc oxide with water and ultrasonically dispersing to obtain a nano zinc oxide solution; The ultrasonic dispersion time is preferably 10 to 120 minutes, more preferably 20 to 100 minutes, and more preferably 30 to 60 minutes; ultrasound can ensure uniform dispersion of zinc oxide; the immersion is preferably carried out under a negative pressure environment of 0.06 to 0.1 MPa, and more preferably under a negative pressure environment of 0.08 MPa; the immersion time is preferably 10 to 30 minutes, and more preferably 20 to 30 minutes; the drying temperature is preferably 50°C to 70°C, more preferably 55°C to 65°C, and more preferably 60°C; the drying time is preferably 1 to 2 hours.
[0046] The hydrogel solution containing nano zinc oxide is covered on both surfaces of the expanded polytetrafluoroethylene film layer, and after freeze drying and thawing treatment, an expanded polytetrafluoroethylene film layer composited with the first hydrogel layer and the second hydrogel layer is obtained; the hydrogel solution containing nano zinc oxide is obtained by mixing a polyvinyl alcohol solution containing nano zinc oxide with an alginate solution; the mass concentration of polyvinyl alcohol in the polyvinyl alcohol solution containing nano zinc oxide is preferably 8% to 12%, more preferably 9% to 11%, and more preferably 10%; the molecular weight of the polyvinyl alcohol is preferably 50000 to 100000, more preferably 60 000~90000, more preferably 70000~85000, most preferably 72600~81400; the concentration of nano zinc oxide in the polyvinyl alcohol solution containing nano zinc oxide is preferably 1~3g / L, more preferably 1~2g / L; the mass concentration of alginate in the alginate solution is preferably 1%~3%, more preferably 1.5%~2.5%, more preferably 2%; the alginate is preferably sodium alginate; the viscosity of the alginate is preferably 100~200mPa·s, more preferably 120~180mPa·s, more preferably 140~1 60mPa·s, most preferably 150mPa·s; the mass ratio of the polyvinyl alcohol solution containing nano zinc oxide to the alginate solution is preferably (7-9):(3-1), more preferably (7.5-8.5):(2.5-1.5), and more preferably 8:2; the mixing method can be a method well known to those skilled in the art, and there is no special limitation. In the present invention, ultrasonic mixing is preferably used; the time of ultrasonic mixing is preferably 10-120min, more preferably 30-120min, more preferably 60-120min, and most preferably 90-120min ; The covering method is any method well known to those skilled in the art and is not particularly limited, and may specifically be immersion, coating or electrospinning, etc.; The freeze-drying temperature is preferably -10°C to -30°C, more preferably -15°C to -25°C, and more preferably -20°C; The freeze-drying time is preferably 4 to 8 hours, more preferably 6 to 8 hours; The thawing treatment is carried out at room temperature; In order to improve the stability of the hydrogel layer, it is preferred to repeat the freeze-drying and thawing steps after the thawing treatment; The freeze-drying and thawing treatments are preferably repeated 1 to 3 times, more preferably 1 to 2 times.
[0047] In a specific embodiment provided by the present invention, the covering method is immersion, specifically: first immerse one side of the ePTFE membrane in the configured hydrogel solution, take it out and turn the immersed surface upward, and pre-freeze (freeze at -20°C for 10 to 30 minutes) to prevent the hydrogel solution from flowing, then take it out and immerse the other side, turn the immersed surface upward, and then freeze-dry; this method does not control the thickness.
[0048] In a specific embodiment provided by the present invention, the covering method is coating, specifically: coating the hydrogel solution on one side of the ePTFE membrane, pre-freezing it first, taking it out and coating the other side, and then freeze-drying it. This method does not control the thickness.
[0049] In another specific embodiment provided by the present invention, the covering method is electrospinning, specifically: using an electrospinning machine, the spinning solution is the prepared hydrogel solution, and spinning is performed on both sides of the ePTFE membrane until both sides of the ePTFE membrane are covered with fibers. This method does not control the thickness.
[0050] The polymer mesh is sutured to the surface of the second hydrogel layer in the expanded polytetrafluoroethylene film layer that composites the first hydrogel layer and the second hydrogel layer; the polymer mesh is preferably a polymer warp knitted mesh; the thickness of the polymer mesh is preferably 0.4-0.8 mm; the pore size of the polymer mesh is preferably 0.1-2 mm; the polymer mesh is preferably a polyvinylidene fluoride (PVDF) mesh or a polypropylene (PP) mesh; the suture is preferably performed using polytetrafluoroethylene (PTFE) sutures.
[0051] After suturing the polymer mesh, it is preferred to cover the edge of the polymer mesh with a hydrogel solution containing nano zinc oxide, and perform freeze drying and thawing treatment; the hydrogel solution containing nano zinc oxide is the same as described above, wherein the concentration of each substance can be the same as or different from the concentration of the hydrogel containing nano zinc oxide used in step S2), and there is no special restriction; the covering method can be a method well known to those skilled in the art, and there is no special restriction, specifically immersion, coating or electrospinning, etc.; the freeze drying temperature is preferably -10°C to -30°C, more preferably -15°C to -25°C, and more preferably -20°C; the freeze drying time is preferably 4 to 8 hours, more preferably 6 to 8 hours; the thawing treatment is carried out at room temperature; in order to improve the stability of the hydrogel layer, it is preferred to repeat the freeze drying and thawing steps after the thawing treatment; the freeze drying and thawing treatments are repeated preferably 1 to 3 times, more preferably 2 to 3 times.
[0052] Finally, the device is preferably immersed in a calcium ion solution and dried to obtain an antibacterial repair device; the concentration of calcium ions in the calcium ion solution is preferably 0.05-0.2 mol / L, more preferably 0.1 mol / L; the calcium ion solution is preferably a calcium salt solution, more preferably a calcium chloride solution; the immersion treatment time is preferably 4-8 h, more preferably 5-7 h, and more preferably 6 h; after the immersion treatment, it is preferably washed and then dried; the washing is preferably carried out with deionized water; excess calcium salt can be removed by washing; the drying temperature is preferably 40°C-50°C, more preferably 45°C; the drying is preferably carried out until the quality is stable.
[0053] The present invention effectively removes the air in the micropores of the expanded polytetrafluoroethylene membrane through vacuum extraction technology, avoiding the obstruction of the air in the micropores to the adhesion of zinc oxide, thereby improving the antibacterial effect. In this way, even if pathogens penetrate the antibacterial hydrogel and enter the micropores in the membrane, they can be effectively inhibited to prevent infection.
[0054] In order to further illustrate the present invention, an antibacterial repair device and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments.
[0055] The reagents used in the following examples are all commercially available; the PVA used in the examples is PVA1799, with a molecular weight of 72600-81400; and the viscosity of sodium alginate is 150 mPa·s.
[0056] Example 1
[0057] Prepare a nano zinc oxide solution with a concentration of 1 g / L, and disperse it by ultrasonic for 30 minutes before use;
[0058] Take an ePTFE membrane with a pore size of ≤5μm and a thickness of 1mm and soak it in a zinc oxide solution. Put the zinc oxide solution soaked with ePTFE into a vacuum device and soak it in a negative pressure environment of 0.08MPa for 30min. Then take out the ePTFE membrane and put it into a drying oven at 60℃ for 1h to obtain an ePTFE membrane A loaded with zinc oxide particles.
[0059] Take an ePTFE membrane with a pore size of ≤5 μm and a thickness of 1 mm, soak it in a zinc oxide solution at room temperature and pressure for 30 minutes, take out the ePTFE membrane, and place it in a drying oven at 60° C. for 1 hour to obtain an ePTFE membrane B loaded with zinc oxide particles.
[0060] The antibacterial properties of membranes A and B were investigated using the plate counting method. The results are shown in Tables 1 and 2.
[0061] Table 1 Antibacterial effect on Staphylococcus aureus
[0062]
[0063] Table 2 Antibacterial effect on Escherichia coli
[0064]
[0065] It can be seen from the table that the antibacterial performance of the ePTFE membrane soaked in vacuum is better.
[0066] In addition, an in vitro release test of ePTFE membrane A loaded with zinc oxide particles was conducted, and the zinc oxide release curve was obtained as shown in FIG. Figure 3 shown.
[0067] Among them, the in vitro release test of zinc oxide was determined by UV-visible spectrophotometry: first, the characteristic peak of ultraviolet absorption of zinc oxide was determined by ultraviolet absorption spectrometer, and a standard curve was prepared using a specific concentration of zinc oxide according to the characteristic peak. Then, the ePTFE membrane loaded with zinc oxide particles was immersed in 5mL PBS solution (pH value of 7.2-7.4) in groups, and the liquid was taken out in 1-12 hours and the absorbance of the immersion liquid at the characteristic peak was detected by an enzyme marker. The measured absorbance was converted into ZnO content according to the standard curve to make a curve.
[0068] From Tables 1, 2 and Figure 3 It shows that zinc oxide is embedded in ePTFE membrane A, which can quickly release a large amount of zinc oxide within 12 hours. This rapid release property gives the membrane instant antibacterial efficacy, which can quickly inhibit the growth and reproduction of bacteria and provide effective antibacterial protection in the initial stage.
[0069] Example 2
[0070] Prepare a 10% PVA solution by mass, add nano zinc oxide, and the amount of zinc oxide added is 1 g / L; prepare a 2% sodium alginate solution by mass, take 8 parts of PVA solution and 2 parts of alginate solution and blend them, disperse them by ultrasound (power is 28KHz) for 120 minutes and set them aside.
[0071] The hydrogel solution was frozen at -20°C for 8 hours, taken out and thawed once at room temperature, and repeated three times to form a gel. The entire membrane was then immersed in a 0.10 mol / L CaCl2 solution for 6 hours, taken out and rinsed off excess CaCl2 with deionized water, and then placed in a constant temperature drying oven at 45°C until the gel quality no longer changed.
[0072] The gel was used for in vitro release experiment, and the zinc oxide release curve was drawn as follows: Figure 4 shown.
[0073] Depend on Figure 4 It can be seen that the hydrogel film of the present invention contains zinc oxide, which can achieve slow release of zinc oxide within 14 days, thereby providing a long-lasting antibacterial effect. This slow release mechanism ensures that the antibacterial component is evenly distributed in the surrounding environment over a long period of time, effectively inhibits bacterial growth, and enhances the antibacterial performance of the repair device.
[0074] Example 3
[0075] A. Preparation of antibacterial ePTFE membrane:
[0076] 1) Prepare 1 g / L nano zinc oxide solution and disperse it by ultrasonic for 30 minutes to ensure uniform dispersion.
[0077] 2) Select an ePTFE membrane with a pore size of no more than 5 μm and a thickness of 1 mm, immerse it in the above zinc oxide solution, and then place the entire membrane in a vacuum device at a negative pressure of 0.08 MPa for 30 minutes.
[0078] 3) The ePTFE membrane was taken out and dried in a drying oven at 60° C. for 1 hour, and finally an ePTFE membrane loaded with antibacterial zinc oxide particles was obtained.
[0079] B. Preparation of antibacterial hydrogel solution:
[0080] 1) Prepare a 10% mass fraction polyvinyl alcohol (PVA) solution and add 1 g / L nano zinc oxide.
[0081] 2) Prepare a 2% sodium alginate solution.
[0082] 3) 8 parts of PVA solution were mixed with 2 parts of sodium alginate solution and dispersed using ultrasound for 120 minutes to prepare a uniform hydrogel solution.
[0083] C. Preparation of ePTFE membrane coated with hydrogel:
[0084] 1) The hydrogel solution prepared in step B is evenly covered on the ePTFE membrane by soaking. Specifically, first soak one side of the ePTFE membrane in the prepared hydrogel solution, take it out and place the soaked side upward, and pre-freeze (freeze at -20°C for 10 to 30 minutes) to prevent the hydrogel solution from flowing, then take it out and soak the other side so that the side faces upward.
[0085] 2) The ePTFE membrane covered with the hydrogel solution was frozen at -20°C for 8 hours.
[0086] 3) After taking out, thaw at room temperature for 3 hours, and repeat the freezing and thawing process once (without re-immersing in the hydrogel solution) to form a stable hydrogel layer.
[0087] D. Preparation and fixation of composite mesh layer:
[0088] 1) Select a warp knitted mesh layer made of PVDF (thickness 0.5 mm, pore size 2 mm).
[0089] 2) Use polytetrafluoroethylene (PTFE) sutures to sew the PVDF mesh layer to the ePTFE membrane coated with the hydrogel prepared in step C.
[0090] 3) Use the hydrogel solution in step B again to cover the edge of the mesh by soaking.
[0091] 4) Freeze the treated membrane at -20°C for 8 hours, take it out and thaw it at room temperature, and repeat this process three times.
[0092] 5) Finally, the product was immersed in a 0.10 mol / L CaCl2 solution for 6 hours, and then taken out and rinsed with deionized water to remove excess CaCl2.
[0093] 6) The treated product is placed in a constant temperature drying oven at 45° C. to dry until the gel quality is stable, thereby obtaining an antibacterial repair device.
[0094] In the animal experiment, the repair device of the present invention (experimental group) and the control sample not covered with hydrogel (control group, the difference between the control group and the experimental group is that the control group is not covered with the top layer of hydrogel (the rest are the same), and the edge of the mesh without a hydrogel layer will cause the jagged edge to be exposed to the outside, which is easy to cause tissue inflammation) were implanted into the animal body. After a 4-week observation period, the animals were killed, and the number of CD3 and CD68 positive cells in the tissue around the implant was detected by immunohistochemistry. The experimental results showed that the number of CD3 positive cells in the control group was significantly higher than that in the experimental group (108.6±24.2 vs. 40.3±10.9, P<0.001). Similarly, the number of CD68 positive cells in the control group was also significantly higher than that in the experimental group (156.2±44.3 vs. 96.7±32.8, P<0.001).
[0095] These results show that the repair device of the present invention significantly reduces the tissue inflammatory response caused by the jagged edges of the mesh by covering the antibacterial hydrogel at the edge of the mesh layer. This design not only improves the biocompatibility of the implant, but also helps to reduce postoperative complications, thereby providing patients with a safer and more effective treatment option.
[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An antibacterial repair device, characterized in that: It comprises a first hydrogel layer, an expanded polytetrafluoroethylene film layer, a second hydrogel layer and a polymer mesh layer which are arranged in sequence; the first hydrogel layer, the expanded polytetrafluoroethylene film layer and the second hydrogel layer are all loaded with nano zinc oxide.
2. The antibacterial repair device according to claim 1, characterized in that: The thickness of the expanded polytetrafluoroethylene film layer is 0.8-2 mm; the pore size of the expanded polytetrafluoroethylene film layer is not greater than 5 μm.
3. The antibacterial repair device according to claim 1, characterized in that: The edge of the polymer mesh layer is covered with a third hydrogel layer; the third hydrogel layer is loaded with nano zinc oxide.
4. The antibacterial repair device according to claim 3, characterized in that: The first hydrogel layer, the second hydrogel layer and the third hydrogel layer are double-crosslinked alginate-polyvinyl alcohol hydrogels loaded with nano zinc oxide; The polymer mesh layer is selected from a polyvinylidene fluoride mesh layer or a polypropylene mesh layer.
5. The antibacterial repair device according to claim 1, characterized in that: The thickness of the first hydrogel layer and the second hydrogel layer are independently 0.6 to 1 mm.
6. A method for preparing an antibacterial repair device, characterized in that: The following steps are involved: S1) soaking the expanded polytetrafluoroethylene film in a nano zinc oxide solution under vacuum conditions, and drying the solution to obtain an expanded polytetrafluoroethylene film layer; S2) covering the two surfaces of the expanded polytetrafluoroethylene film layer with a hydrogel solution containing nano zinc oxide, and after freeze-drying and thawing, obtaining an expanded polytetrafluoroethylene film layer composited with the first hydrogel layer and the second hydrogel layer; S3) Suturing the polymer mesh to the surface of the second hydrogel layer in the expanded polytetrafluoroethylene film layer that composites the first hydrogel layer and the second hydrogel layer to obtain an antibacterial repair device.
7. The preparation method according to claim 6, characterized in that: After the polymer mesh is sutured in step S3), the edge of the polymer mesh is covered with a hydrogel solution containing nano zinc oxide, and after freeze-drying and thawing, an antibacterial repair device is obtained.
8. The preparation method according to claim 7, characterized in that: In the step S3), after freeze-drying and thawing, the product is immersed in a calcium ion solution and dried to obtain an antibacterial repair device.
9. The preparation method according to claim 6, characterized in that: The concentration of the nano zinc oxide solution is 1 to 3 g / L; The pore size of the expanded polytetrafluoroethylene membrane is not greater than 5 μm; the thickness of the expanded polytetrafluoroethylene membrane is 0.8 to 2 mm; The hydrogel solution containing nano zinc oxide is obtained by mixing a polyvinyl alcohol solution containing nano zinc oxide with an alginate solution; The mass concentration of polyvinyl alcohol in the polyvinyl alcohol solution containing nano zinc oxide is 8% to 12%; the concentration of nano zinc oxide in the polyvinyl alcohol solution containing nano zinc oxide is 1 to 3 g / L; the mass concentration of alginate in the alginate solution is 1% to 3%; The mass ratio of the polyvinyl alcohol solution containing nano zinc oxide to the alginate solution is (7-9): (3-1).
10. The preparation method according to claim 6, characterized in that: The immersion in step S1) is carried out under a negative pressure environment of 0.06 to 0.1 MPa; the immersion time is 10 to 30 minutes; The freeze drying temperature in step S2) is -10°C to -30°C; the freeze drying time is 4 to 8 hours; and the thawing process is carried out at room temperature; The freeze drying and thawing steps are repeated after the thawing process in step S2); the freeze drying and thawing processes are repeated 1 to 3 times.
Citation Information
Patent Citations
Compound anti-adhesion herniorrhaphy tablet and manufacturing method thereof
CN102058442A
Double-crosslinked sodium alginate hydrogel and preparation method and application thereof
CN105713106A
Antibacterial hernia repair tablet and preparation method thereof
CN114681684A
Three-layer composite structure repairing material and preparation method thereof
CN118320179A
Antibacterial molding and method for producing the same
JP2021127366A